Perspectives of rural health and human service practitioners following suicide prevention training programme in Australia: A thematic analysis. (8th January 2018) - Jones, Martin; Ferguson, Monika; Walsh, Sandra; Martinez, Lee; Marsh, Michael; Cronin, Kathryn; Procter, Nicolas
Abstract: There are well‐established training programmes available to support health and human services professionals working with people vulnerable to suicide. However, little is known about involving people with lived experience in the delivery of suicide prevention training with communities with increased rates of suicide. The aim of this paper was to report on a formative dialogical evaluation that explored the views of health and human services workers with regard to a suicide prevention training programme in regional (including rural and remote areas) South Australia which included meaningful involvement of a person with lived experience in the development and delivery of the training. In 2015, eight suicide prevention training workshops were conducted with health and human services workers. All 248 participants lived and worked in South Australian regional communities. We interviewed a subsample of 24 participants across eight sites. A thematic analysis of the interviews identified five themes: Coproduction is key, It is okay to ask the question, Caring for my community, I can make a difference and Learning for future training. The overall meta‐theme was "Involvement of a person with lived experience in suicide prevention training supports regional communities to look out for people at risk of suicide." This paper highlights the need for suicide prevention training and other workforce development programmes to include lived experience participation as a core component in development and delivery.